Dungeon of the Emir of Bukhara - Khalikova Nargiza Erkinovna (International Journal on Integrated Education, 2022)
The article provides information about the Emirate's prison in the Emirate of Bukhara, which existed in the XVIII-XX centuries. Information is provided on the location of the Emirate Prison, its structure and current status. Attempts were also made to provide information on who was imprisoned and under what conditions they were detained.